Прогностички фактори кај миелодиспластични синдроми - Сотирова, Татјана (Медицински факултет, УКИМ, Скопје, 2015)
According to WHO, myelodysplastic syndromes are heterogeneous group of diseases, with cytopenias as a result of an ineffective hematopoiesis and dysplastic morphological characteristics in one or more of the cell lines, and an increased risk of progression in acute myeloid leukemia. Until now in the Republic of Macedonia routine cytogenetic analysis of the myelodysplastic patients was not a part of the diagnostic procedures. Therefore it was not possible to classify patients according to WHO classification (from 2008), nor to stratify them in risk categories according to IPSS (from 1997) and R - IPSS (from 2012). Motif for this doctoral dissertation was refinement of the diagnosis of patients with MDS by inclusion of the molecular cytogenetic analysis ‘Multiplex ligation-dependent probe amplification’ (MLPA) in the routine diagnostic practice, enabling contemporary classification, prognostic risk stratification, and individual therapeutic approach to MDS patients. Aims of this study are: introduction of molecular detection of chromosomal abnormalities with the MLPA analysis as standard method in diagnostic procedures in MDS, detection of chromosomal abnormalities in MDS in order to make proper diagnosis, classification, prognostic risk stratification and personalized therapy, detection of JAK2V617F mutation in MDS patients, evaluation of possible relation of chromosomal abnormalities and prognosis of the disease, distribution of MDS patients according to FAB and WHO classifications, and stratification according to IPSS and R-IPSS, evaluation of prognostic significance of age, sex, blast percentage in bone marrow, cytopenias, MCV, transfusion dependency, serum ferritin, LDH, serum albumin, comorbidities, chromosomal abnormalities and JAK2V617F mutation in MDS patients, evaluation of the implication of the prognostic factors on overall survival, progression, transformation in acute myeloid leukemia and therapeutic outcome, correlation of the chromosomal abnormalities with MDS subtypes, correlation of the chromosomal abnormalities with JAK2V617F mutation in MDS, determination of the epidemiological, clinical, hematological and chromosomal characteristics of MDS patients and creation of the new diagnostic algorithm for MDS patients. In this retrospective-prospective study (cohort) are included 70 adult patients (>18years), men and women, with ‘de novo’ and t-MDS, diagnosed at the University Clinic of Hematology in Skopje, from January 2011 till April 2014, with follow-up period of 52 months. Detection of the chromosomal abnormalities was performed at the Faculty of Pharmacy in Skopje, with the method –MLPA with ‘SALSA MLPA probemix P414-A1 MDS’ of diagnostic or prognostic relevance in MDS for the following chromosomes: 3, 5q (EGR1, MIR145, SPARC, MIR146A), 7q (EZH2), 8q (MYC), 11q (KMT2A), 12p (ETV6), 17 (TP53, NF1, SUZ12), 19, 20q (ASXL1) and Y chromosome. Furthermore, the probemix also contains a mutation-specific probe for the JAK2 V617F mutation. So, also detection of JAK2V617F mutation was performed at the Faculty of Pharmacy in Skopje. Diagnosis is based on the criteria according to the recommendations of the International Consensus Working Group from 2007. After that patients are classified according to the FAB and WHO classifications. Risk stratification is made in accordance with IPSS and R-IPSS. Overall survival and transformation to acute myeloid leukemia are followed. In the control group are included all other adult patients older than 18 years, men and women, with ‘de novo’ and t-MDS, diagnosed at the University Clinic of Hematology in Skopje, in the same period, in whom from different reasons it was not possible to perform detection of the chromosomal abnormalities and JAK2V617F mutation. Necessary data for the control group was obtained from the patients’ files. In the cohort of 70 patients, the relation among 17 factors and overall survival was evaluated. The univariate analysis revealed only 4 from 17 factors as predictors of the event and associated with overall survival. The overall survival associated with the platelet number, blast percentage in the bone marrow, IPSS and R-IPSS. Platelets < 100x109/L increase the event in comparison with other platelets. Blast percentage in the bone marrow < 5, IPSS and R - IPSS (very low and low) reduced the event in comparison with the others. Multivariate analysis for overall survival revealed that predictors of the event are platelets < 100x109/L, IPSS - low risk and R - IPSS – intermediate risk. In the control group, the relation among 14 factors and overall survival was evaluated. The univariate analysis revealed only 5 from 14 factors as predictors of the event and associated with overall survival. The overall survival associated only with age, the platelet number, blast percentage in the bone marrow, WHO subtypes and comorbidities. Age < 50 years, blast percentage in the bone marrow < 5% and absence of comorbidities reduce the event in comparison with the others. But, platelets < 100x109/L, WHO subtypes (RAEB - 1, RAEB - 2, CMML - 1) and AML increase the event in comparison with others. Multivariate analysis for overall survival revealed that predictors of the event are age < 50 years and platelets < 100x109/L. In the cohort of 70 patients the chromosomal abnormalities (present or absent) correlate only with hemoglobin and serum ferritin levels and megakaryocytic dysplasia. In conclusion, detection of the chromosomal abnormalities, as one of the key diagnostic procedure has great importance in prediction of overall survival in MDS patients. It enables patients’ distribution according to WHO classification and risk stratification according to IPSS and R - IPSS. So, clinicians can easily determine an adequate therapeutic approach in MDS patients in order to prolong their overall survival. It ought to be mentioned that there is still a significant percentage of patients with normal findings of chromosome analysis. Despite, they are heterogeneous and belong to different FAB and WHO subtypes and different prognosis according to IPSS and R - IPSS. Therefore, the researches lately are focused on gene mutations, aiming to detect mutations with impact on prognosis. That would lead to their incorporation in prognostic systems, enabling refinement of patient’s risk stratification. Due to population, and especially economic reasons, such researches are possible only in developed countries.
Докторска дисертација одбранета во 2015 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Борче Георгиевски.